Hazards of ultra-marathon running in the Scottish highlands: exercise-associated hyponatraemia. Issue 12 (24th November 2009) - Cuthill, J A; Ellis, C; Inglis, A
Abstract : The case histories are presented of four athletes taking part in a 95-mile ultra-endurance foot race in Scotland who were hospitalised after developing exercise-associated hyponatraemia and rhabdomyolysis. Exercise-associated hyponatraemia is relatively uncommon in temperate climates. Risk factors disposing to this disorder are discussed. Exercise-associated hyponatraemia is thought to be due to overconsumption of hypotonic fluid with other associated pathophysiology including an inability to suppress fully antidiuretic hormone during exercise or to mobilise adequate sodium from osmotically inactive internal stores. Non-specific symptoms make this disorder difficult to diagnose on site without the assistance of serum sodium measurement, but any delay in treatment of patients with encephalopathy can prove fatal. Mainstays of treatment include fluid restriction, hypertonic saline, loop diuretics and mannitol.